First detailed insights into the life-history traits of the alien shrimp Athanas nitescens (Decapoda: Alpheidae) in the western Atlantic - Pescinelli, Régis A. [UNESP]; Mantelatto, Fernando L.; Almeida, Alexandre O.; Costa, Rogerio C. [UNESP] (Wiley, 2021)
Information on the population biology of alien species in non-natural areas is essential to understanding their impacts on native species. Here, we investigated the life-history traits, the propagule pressure and the supply potential of Athanas nitescens in a non-native area. Sampling was monthly performed from April 2015 to March 2016 in an inter-tidal estuary in the south-eastern Brazilian coast. The population had a female-biased sex ratio with a predominance of ovigerous females. Sexual dimorphism was evidenced by the mean body size and the positive allometry of chelipeds in males and of the second pleonal pleuron in females, evidencing an energy allocation to weaponry body structures and reproduction, respectively. The estimated size at which 50% of females reach functional sexual maturity was 3.3 mm of carapace length. The mean fecundity, 117 ± 40.03 eggs/female (53–263), had a positive correlation with the carapace length. The egg volume increased (83%) from the initial to the final stage of development. The presence of females carrying eggs in different stages of development indicates that A. nitescens is completing its life cycle in the studied region and shows a high propagule pressure. We provided the first insights into the biology of A. nitescens in Brazilian waters after the first record in 2009 in São Paulo coast, contributing to a better understanding of its biology and ecology in non-natural areas.
Keywords: Caridea; dispersion; egg volume; fecundity; propagule pressure; relative growth